Recognizing the Effect of Profitability as a Moderator in Determining Stock Price Changes - Nirsetyo Wahdi; Pantun; Adria Wuri Lestari; Aprih Santoso; Dipa Teruna Awaludin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Industrial development plays an important role in supporting Indonesia’s economic growth, particularly in the property sector, which attracts increasing investor interest. This study examines the effect of the price earnings ratio, current ratio, and debt to equity ratio on stock prices of property sector companies listed on the Indonesia Stock Exchange, with return on assets as a moderating variable. The study uses panel data from 12 property companies over the 2018–2022 period. Panel data regression with moderation analysis is applied using EViews version 12. The results indicate that the price earnings ratio and return on assets have a significant effect on stock prices, while the current ratio and debt to equity ratio do not show a significant influence. The moderation analysis reveals that Return on Assets strengthens the relationship between the price earnings ratio and stock prices, but does not moderate the effects of liquidity and leverage ratios. The coefficient of determination shows that the independent and moderating variables explain 37.58 % of stock price variation, while the remaining variation is influenced by other factors not examined in this study. These findings provide useful insights for investors and related institutions in evaluating stock price movements in the property sector.